Belief and truth a skeptic reading of Plato - Vogt, Katja Maria, 1968- (New York ; Oxford : Oxford University Press, 2012)
'Belief and Truth' explores a Socratic intuition about belief doxa - belief is 'shameful.' In aiming for knowledge, one must aim to get rid of beliefs. Vogt shows how deeply this proposal differs from contemporary views, but that it nevertheless speaks to intuitions we are likely to share with Plato, ancient skeptics, and Stoic epistemologists.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Plato; Knowledge, Theory of; Skepticism; Belief and doubt; Truth